A genetic algorithm approach for global routing of VLSI circuits - Ravikumar, D; Raaza, Arun; Devi, V; Gopinathan, E (International Journal of Engineering and Technology, 2018)
Very Large Scale Integrating (VLSI) design has the objectives of producing the layout for integrating circuits. The currently prevalent submicron regions require innovative, new physical design algorithms. Performance requirements have not seen before, become the significant features of such regions. The last ten years have been witnessing the feature of swelling success of Genetic Algorithms in their application to VLSI physical design. These algorithms are in spot light and the subject matter of study and examination. Routing problem is posed to a cost function which takes care of the total net length, the channel capacity exceedance and crosstalk. The Genetic algorithm is used for optimizing the cost function.Â Â